Chronic abruption as a differential diagnosis of succenturiate placenta. Case report - Bernardo T. Santander-Bastidas; Ivan R. Angulo-Quiñones; Carolina Agudelo-Otero; Juan D. Ibagon-Bedoya; Jorge R. Paredes-Aguirre (Revista Chilena de Obstetricia y Ginecología)
Chronic abruption-oligohydramnios sequence (CAOS) is clinically characterized by a triad: clinically significant vaginal bleeding without an identifiable source, amniotic fluid volume initially documented as normal, and oligohydramnios that eventually develops without evidence of ruptured membranes. This case report presents a 43-year-old patient in her first pregnancy, 28.3 weeks, with associated comorbidities, who experienced several episodes of moderate-to-severe vaginal bleeding. She was clinically and radiologically diagnosed with chronic placental abruption, leading to expectant management. At 35.5 weeks, she underwent a cesarean section due to a new episode of bleeding. However, the placental evaluation revealed no signs of abruption as previously observed in imaging studies; instead, it showed a placenta succenturiata with two accessory lobes and an area of ecchymosis likely corresponding to the site of clot containment described in the ultrasounds. The placenta was sent for further studies, and the pathology report indicated normal findings. There is a need for careful differential diagnosis to identify the causes of bleeding in the second half of pregnancy, as they can impact management and outcomes.